2018
DOI: 10.3389/fchem.2018.00049
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Food Integrity by Metrology and FAIR Data Principles

Abstract: Food integrity is a general term for sound, nutritive, healthy, tasty, safe, authentic, traceable, as well as ethically, safely, environment-friendly, and sustainably produced foods. In order to verify these properties, analytical methods with a higher degree of accuracy, sensitivity, standardization and harmonization and a harmonized system for their application in analytical laboratories are required. In this view, metrology offers the opportunity to achieve these goals. In this perspective article the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…More than 300 Alternaria species have been described to cause diseases in more than 400 plant species (Meena et al , ; Pinto and Patriarca, ; Rychlik et al , ). A. alternata alone infects already more than 100 plant species, and therefore, is an economically important food and feed contaminating fungus (Lee et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 300 Alternaria species have been described to cause diseases in more than 400 plant species (Meena et al , ; Pinto and Patriarca, ; Rychlik et al , ). A. alternata alone infects already more than 100 plant species, and therefore, is an economically important food and feed contaminating fungus (Lee et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The Novel Food Systems outlined above (e.g., Sustainable Food systems, Cellular Agriculture) open a perspective to the agri-food “community” to supply foods of high integrity, i.e., being sound, nutritious, healthy, tasty, safe, authentic, traceable, as well as ethically, safe, environment-friendly, and sustainably produced ( 281 ).…”
Section: Food Processing and Manufacturingmentioning
confidence: 99%
“…Nevertheless, food analysis of the future increasingly has to include chemometry and, for validation of the results, also metrology, i.e., “the science of measurement, embracing both experimental and theoretical determinations at any level of uncertainty in any field of science and technology” ( 284 ). With respect to metrology, METROFOOD-RI, the pan-European Research Infrastructure for promoting Metrology in Food and Nutrition aims to promote scientific excellence in the field of food quality and safety ( 281 ). METROFOOD-RI recently has been approved by the ESFRI (European Strategy Forum on Research Infrastructures) and started its preparatory phase to become operational soon.…”
Section: Food Processing and Manufacturingmentioning
confidence: 99%
“…It has also been suggested that FAIR data may be useful in addressing the need to generate and share high-quality data to facilitate the World Health Organization elimination goals for neglected tropical diseases [ 29 ]. Much work has been conducted to implement the FAIR principles in other domains, such as computational workflows [ 30 ], food and nutrition [ 31 ], materials science [ 32 ], and oceanography [ 33 ].…”
Section: Introductionmentioning
confidence: 99%